Quantitative Magnetic Separation of Particles and Cells Using Gradient Magnetic Ratcheting. Issue 14 (17th February 2016) - Murray, Coleman; Pao, Edward; Tseng, Peter; Aftab, Shayan; Kulkarni, Rajan; Rettig, Matthew; Di Carlo, Dino
Abstract : Extraction of rare target cells from biosamples is enabling for life science research. Traditional rare cell separation techniques, such as magnetic activated cell sorting, are robust but perform coarse, qualitative separations based on surface antigen expression. A quantitative magnetic separation technology is reported using high‐force magnetic ratcheting over arrays of magnetically soft micropillars with gradient spacing, and the system is used to separate and concentrate magnetic beads based on iron oxide content (IOC) and cells based on surface expression. The system consists of a microchip of permalloy micropillar arrays with increasing lateral pitch and a mechatronic device to generate a cycling magnetic field. Particles with higher IOC separate and equilibrate along the miropillar array at larger pitches. A semi‐analytical model is developed that predicts behavior for particles and cells. Using the system, LNCaP cells are separated based on the bound quantity of 1 μm anti‐epithelial cell adhesion molecule (EpCAM) particles as a metric for expression. The ratcheting cytometry system is able to resolve a ±13 bound particle differential, successfully distinguishing LNCaP from PC3 populations based on EpCAM expression, correlating with flow cytometry analysis. As a proof‐of‐concept, EpCAM‐labeled cells from patient blood are isolated with 74% purity, demonstrating potential toward a quantitative magnetic separation instrument. Abstract : Arrays of embedded micromagnets that miniaturize and amplify magnetic field gradients enable ratcheting motion of magnetic particles and cells in the presence of an oscillating magnetic field. By incrementing the pitch of the array along its length, particles with different magnetic content transit and equilibrate at different spatial locations, enabling analysis and equilibrium separations similar to flow cytometry.